2009
DOI: 10.1016/j.bbrc.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fatty acids stimulate and insulin suppresses CIDE-A expression in bovine mammary epithelial cells

Abstract: Cell death-inducing DNA fragmentation factor-alpha-like effector A (CIDE-A) was first identified by its sequence homology with the N-terminal domain of DNA fragmentation factor (DFF). CIDE-A negatively regulates the activity of uncoupling protein 1 (UCP1) in brown adipose tissue. CIDE-A and UCP1 mRNA were detected by RT-PCR in cloned bovine mammary epithelial cells (bMEC) and lactating bovine mammary glands. Physiological concentrations of saturated fatty acids (stearate and palmitate), but not unsaturated fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…These results suggest that the observed effects of insulin on CIDE mRNA expression may not result from differentiation or PPAR ␥ -directed transcription. It has recently been reported that insulin suppresses CIDEA expression in bovine mammary epithelial cells ( 40 ) and increases CIDEC expression in mouse 3T3-L1 adipocytes ( 36 ). These reports support our fi ndings in human adipocytes.…”
Section: Cidec Depletion Prevents Insulin-induced Enlargement Of Lipisupporting
confidence: 92%
“…These results suggest that the observed effects of insulin on CIDE mRNA expression may not result from differentiation or PPAR ␥ -directed transcription. It has recently been reported that insulin suppresses CIDEA expression in bovine mammary epithelial cells ( 40 ) and increases CIDEC expression in mouse 3T3-L1 adipocytes ( 36 ). These reports support our fi ndings in human adipocytes.…”
Section: Cidec Depletion Prevents Insulin-induced Enlargement Of Lipisupporting
confidence: 92%
“…Fatty acid-binding protein (FABP) regulates the channeling of fatty acids toward copious milk fat synthesis in bovine mammary gland [43]. The expression level of CIDE-A protein was regulated by insulin and/or fatty acids in mammary epithelial cells, and thereby played an important role in lipid and energy metabolism [44]. Acyl-coa synthetase long-chain family member 1 (ACSL1) which involves in fatty acid analysis [43] was differentially expressed in lactation,.…”
Section: Discussionmentioning
confidence: 99%
“…As for the roles of CIDEs in lipid metabolism, CIDE family proteins have been categorized as lipid droplet‐associated proteins . In order to facilitate research on lipid droplet associated‐proteins, FFAs are often used to increase intracellular lipid droplets . What is more, prolonged incubation with FFAs has a devastating impact on beta cell viability .…”
Section: Resultsmentioning
confidence: 99%
“…The first known function of CIDEs was promotion of apoptosis upon ectopic expression in mammalian cells . However, recent studies in endogenous settings demonstrated key roles for CIDEs in energy metabolism . Our previous studies proved that Cideb could act as a metabolic sensor to respond to varying metabolic conditions and regulate multiple lipid metabolism pathways including fatty acid synthesis, storage and lipid secretion in livers .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation